ITS ON RAILWAY - Martin Leso (Acta Polytechnica CTU Proceedings, 2017)
Development of technology management and security, transmission and information systems allows the concept of process management and security of railways and organizing the operation of a new, as yet non-phase in a non-traditional way. Requirements for higher efficiency, accuracy and flexibility of the attractiveness of rail transport Connection in the integrated transport systems are a challenge for the railways. These requirements can be solved just by changing the concept and technology of the presented here as an ITS-R.